A Study of Coupled Fixed Point in Multiplicative \(S\)-Metric Space - Gandhi, Manjusha P.; Aserkar, Anushree A.; Chib, Shiney (Communications in Mathematics and Applications, 2024)
This study presents a novel common coupled fixed point result for two mappings in multiplicative \(S\)-metric space. Uniqueness of this point is proven through the utilization of a compatibility condition, validated through a provided example. Additionally, an application to integral equations is discussed within this article.
Keywords: Coupled fixed point; Compatible mappings; Multiplicative S-metric space